"One of life and one of death" apocalypticism and the Didache's two ways - Wilhite, Shawn J. (Gorgias Press, 2019)
"This book explores the apocalyptic influence upon the Two Ways metaphor in antiquity and more particularly the influence of the Two Ways in the Didache as veering from an apocalyptic worldview. The argument includes essential critical evaluation of the apocalyptic genre and assesses the apocalyptic features in ancient Two Ways texts. The predominant focus of the book will document and critically assess how the Didache veers from maintaining an apocalyptic worldview in its expression of the Two Ways (Did. 1-6)"--
Keywords: Didache / Commentaries; Apocalyptic literature; Church history / Primitive and early church, ca. 30-600; Didache; Church history / Primitive and early church; 30-600